Journal Economics, business & accountancy : INCREASING THE EMPLOYEES’ PERFORMANCE THROUGH TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE AT PT. PERKEBUNAN NUSANTARA V RIAU - Marnis (PPPM Perbanas, 2013)
The research is conducted at PT. Perkebunan Nusantara V (PTPN V) Riau. It has some objectivessuch as to examine and analyze (1) the effect of transformational leadership and organizationalculture on employee performance, (2) the effect of transformational leadershipand organizational culture on organizational commitment, and (3) the effect of organizationalcommitment on employee performance. The population taken consists of 146 peoplecovering middle managers.